Conflict, democratization, and the Kurds in the Middle East Turkey, Iran, Iraq, and Syria - Romano, David; Romano, David; Gurses, Mehmet; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This volume examines how the Kurdish issue has acted as both an impediment and impetus to democratization in Turkey, Iran, Iraq, and Syria.
Keywords: Science; Science; Science, general